Evaluation of vibrodiagnostic optimization model for turbo pumps. (November 2022) - Milovancevic, Milos; Denic, Nebojsa; Vracar, Ljubomir; Kojic, Nenad; Kostic, Vladimir; Bacevac, Srecko
Highlights: Optimization of the vibrodiagnostic model. determining the probability of occurrence of a certain defect in turbo pumps. relationships between diagnostic models and defined values of target functions. Abstract: Optimization of the vibrodiagnostic model implies defining the minimum number of vibrodiagnostic formats, with which one can unambiguously and unambiguously diagnose a wide range of errors on all types of rotary machines, ie turbo pumps in standard use. In this research, optimization is viewed more from the aspect of the new formulation of the optimization problem, than from the aspect of the mathematical apparatus for solving the problem. Optimization in this case is based on determining the probability of occurrence of a certain defect in turbo pumps and the implementation of causal relationships between diagnostic models and defined values of target functions.